2020
DOI: 10.1111/jcmm.16149
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 is a potential prognostic predictor of glioma

Abstract: Zhong-run Qian 1 This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…We further explored the potential relationships between NOP2 and immunity mainly including four aspects (tumor microenvironment, tumor immune infiltration, immune cell pathway, and immune checkpoint molecules). As reported by previous articles, tumor microenvironment as well as tumor immune infiltration was associated with ccRCC prognosis and response to immunotherapy [ 49 , 50 ] and various genes had been found to be significantly associated with immune cells pathways and checkpoint molecules [ 51 , 52 ]. As for tumor immune infiltration, NOP2 was significantly associated with CD4 + T cells, B cells, neutrophil cells, CD8 + T cells and dendritic cells infiltration.…”
Section: Discussionmentioning
confidence: 86%
“…We further explored the potential relationships between NOP2 and immunity mainly including four aspects (tumor microenvironment, tumor immune infiltration, immune cell pathway, and immune checkpoint molecules). As reported by previous articles, tumor microenvironment as well as tumor immune infiltration was associated with ccRCC prognosis and response to immunotherapy [ 49 , 50 ] and various genes had been found to be significantly associated with immune cells pathways and checkpoint molecules [ 51 , 52 ]. As for tumor immune infiltration, NOP2 was significantly associated with CD4 + T cells, B cells, neutrophil cells, CD8 + T cells and dendritic cells infiltration.…”
Section: Discussionmentioning
confidence: 86%
“…ese data reflected the heterogeneity of tumor immune microenvironment between high and low ICI score LGG tissues. Immunotherapies with blockage of immune checkpoints have displayed clinical efficacy in LGG [37]. Here, high ICI scores were characterized by decreased immune activity genes including GZMA, TBX2, TNF, PRF1, IFNG, CXCL9, and CXCL10 as well as reduced immune checkpoint genes including LAG3, CD274, IDO1, PDCD1, HAVCR2, and CTLA4.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have also reported that EZH2 is involved in a novel miR-490-3p/TGIF2/TGFBR1 axis inducing migration and EMT in glioblastomas [15]. EZH2 is also connected with glioma proliferation and metastasis and has been regarded as a potential predictor and therapeutic target in glioma [26,27]. In general, EZH2 could be a marker associated with EMT in glioma.…”
Section: Discussionmentioning
confidence: 99%